Encyclopedia of gastroenterology - Johnson, Leonard R., 1942- (Academic Press, 2004)
This comprehensive three-volume encyclopedia is a comprehensive study of the entire digestive pathway, with nearly 500 focused articles. Each specific anatomical site such as the esophagus, stomach, liver, and pancreas is covered in its own subject area. The biology of gastroenterology is dealt with in areas such as anatomy and development, cell biology, and hormones, while clinical issues are also thoroughly covered in sections such as surgery, cancer, parasitology, and radiology and endoscopy. The Associate Editors include: David H. Alpers, Kim E. Barrett, John M. Carethers, Mark Feldman, Gregory J. Gores, Richard J. Grand, Martin F. Kagnoff, Rodger A. Liddle, Shelly Lu, James Lee Madara, Charles M. Mansbach II, Alexander R. Margulis, John A. Williams, Douglas W. Wilmore, and Jackie D. Wood. This stellar reference work will appeal to academic and clinical gastroenterologists, nephrologists, endocrinologists, physiologists, hepatologists, as well as general medical practitioners and nutritionists. * Only comprehensive work on the market covering all aspects of gastroenterology * Contains over 475 articles ranging from pediatrics to radiology, cancer to nutrition * Written to be accessible to clinical and academic audiences * Developed under the direction of a distinguished board of editors, with articles written by experts in their field * Numerous illustrations, including color figures, support and amplify the article content.